Fibroelastoma as a Culprit of Syncope - Giuliano De Portu; L. Connor Nickels; Eike Flach; Latha Ganti Stead (Case Reports in Critical Care)
We present a case of a valvular mass diagnosed by emergency department bedside ultrasonography in a young patient with syncope. Bedside ultrasound has become a valuable tool in the evaluation of patients with syncope in the emergency department. This patient was believed to have a fibroelastoma on ultrasound that was confirmed by magnetic resonance and ultimately by postsurgical pathological evaluation. The indications and findings of using ultrasonography as part of the workup of syncope in the emergency department are discussed.